Effect of Age on Audio-Visual and Whole Body Reaction Time - G.B. Taware, M.V. Bhutkar, P.M. Bhutkar, V.P. Doijad, A.D. Surdi (Al Ameen Medical College, 2012)
Objectives: With advancing age the incidence of falls and thereby morbidity goes on increasing. One important aspect of increase in the incidence of these mishaps may be the effect of age on reaction time. Background: Hence, the present study was undertaken to study the effect of advancing age on auditory, visual and whole body reaction times. Method: 120 Normal healthy male subjects were distributed in four groups according to age and their Audio-Visual and whole body reaction time were found out with the help of Audio-Visual reaction time apparatus, whole body reaction time apparatus and Digital chronoscope. Results: Assessed by using "ANOVA" single factor analysis test. It was found that audio-visual reaction time and whole body reaction time increases as the age advances and delayed average audio-visual and whole body reaction time is significantly different among different age groups. Effect of ageing on the myelination of neurones may be the possible cause for this observation. Conclusion: Delayed Audio-Visual and whole body reaction time in these subjects suggests that that they should be more cautious during general movements as well as during driving. Also, more stringent tests should be taken for driving license renewal in higher age groups.